Health care utilization outcomes in patients with blunt chest wall trauma following discharge from the emergency department: A retrospective, observational data-linkage study - Ceri Battle (Journal of Trauma and Acute Care Surgery, 2023)
Background : Whilst much is published reporting clinical outcomes in the patients with blunt chest wall trauma who are admitted to hospital from the ED, less is known about the patients’ recovery when they are discharged directly without admission. The aim of this study was to investigate the healthcare utilisation outcomes in adult patients with blunt chest wall trauma, discharged directly from ED in a trauma unit in the UK. Methods : This was a longitudinal, retrospective, single-centre, observational study incorporating analysis of linked datasets, using the Secure Anonymised Information Linkage (SAIL) databank for admissions to a trauma unit in the Wales, between 1st January 2016 and 31st December 2020. All patients aged ≥16 years with a primary diagnosis of blunt chest wall trauma discharged directly home were included. Data was analysed using a negative binomial regression model. Results : 3205 presentations to the ED were included. Mean age was 53 years, 57% were male, with the predominant injury mechanism being a low velocity fall (50%). 93% of the cohort sustained between 0-3 rib fractures. 4% of the cohort were reported to have COPD, and 4% using pre-injury anticoagulants. On regression analysis, inpatient admissions, outpatient appointments and primary care contacts all significantly increased in the 12-week period post-injury, compared with the 12-week period pre-injury (OR: 1.63 95% CI: 1.33-1.99, p < 0.001; OR: 1.28, 95% CI: 1.14-1.43, p < 0.001; OR: 1.02. 95% CI: 1.01-1.02, p < 0.001 respectively). Risk of healthcare resource utilisation increased significantly with each additional year of age, COPD and pre-injury anti-coagulant use (all p < 0.05). Social deprivation and number of rib fracture did not impact outcomes. Conclusion : The results of this study demonstrate the need for appropriate signposting and follow-up for patients with blunt chest wall trauma presenting to the ED, not requiring admission to the hospital.